2010
DOI: 10.1016/j.neuroscience.2010.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aerobic exercise training on cognitive function and cortical vascularity in monkeys

Abstract: This study examined whether regular exercise training, at a level that would be recommended for middle-aged people interested in improving fitness could lead to improved cognitive performance and increased blood flow to the brain in another primate species. Adult female cynomolgus monkeys were trained to run on treadmills for one hour a day, 5 days a week, for a 5 month period (n=16; 1.9±0.4 miles/day). A sedentary control group sat daily on immobile treadmills (n=8). Half of the runners had an additional sede… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
118
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(127 citation statements)
references
References 67 publications
6
118
0
3
Order By: Relevance
“…Improvement in cognitive function is correlated with changes in plasticity-related genes and growth factors [33], neurogenesis [36], and endothelial cell proliferation [37]. Aerobic exercise has also been shown to induce cortical angiogenesis and improve executive function in middle-aged Cynomolgus monkeys [38].…”
Section: Ee Exercise and Stroke Recoverymentioning
confidence: 99%
“…Improvement in cognitive function is correlated with changes in plasticity-related genes and growth factors [33], neurogenesis [36], and endothelial cell proliferation [37]. Aerobic exercise has also been shown to induce cortical angiogenesis and improve executive function in middle-aged Cynomolgus monkeys [38].…”
Section: Ee Exercise and Stroke Recoverymentioning
confidence: 99%
“…Activity-induced neurogenesis has a major impact on cognitive function and on the size of brain components. For example, performance in memory and spatial learning tasks improves following APA in non-human taxa such as monkeys [30] and rodents [8,31,32]. In humans, aerobic fitness is positively correlated with hippocampal and basal ganglia volume in children and older adults [25,33,34], with grey matter density in the insula of young adults [35], as well as with the amount of grey and white matter in the frontal lobe and other brain areas of older adults [27].…”
Section: Effects Of Aerobic Physical Activity On the Brain: Proximatementioning
confidence: 99%
“…One cross-sectional study indicated that higher fitness is related to larger frontal and temporal volumes of grey matter (Colcombe et al 2006). Other potential mechanisms may involve more endotheliumdependent vasodilatation as a result of more NO bioavailability (Green et al 2004) and/or cerebral angiogenesis (Rhyu et al 2010;Swain et al 2003;Ding et al 2006;Black et al 1990). In support of this, ageinduced cerebral atrophy appears to be less marked in those with higher aerobic fitness (Colcombe et al 2003).…”
Section: Introductionmentioning
confidence: 99%